Multifunktionalitet hos prepositionen till - Wendt, Bo-A. (Nordiske Studier i Leksikografi, 2004)
Multifuctionality of the Sw. preposition till ’to’. We usually distinguish between content words and form words. Even though the latter have more vague senses, they have enough lexical meaning for us to recognise in principal the same sense development processes for these as for content words. In the case of Sw. till ’to’, it is here claimed that the sense development can be described in two basic dimensions: 1) within its original sense sphere it has developed other space related senses, as ’direction’ and ’place’ (beside the original ’goal’), and 2) outside this space sphere it has developed metaphorical more abstract senses as ’time limit’, ’result’, ’purpose’ i. a. Nevertheless, form words are quite different from content words, in that manner that they altogether cover only a few and very basic senses which futhermore overlap between the words – thereby forming a special lexicographic challenge.